Behind the Eight Ball : Sex for Crack Cocaine Exchange and Poor Black Women. - Telfair Sharpe, Tanya (Taylor and Francis, 2012)
Inner-city black women open their hearts to share the pain of crack addiction and its consequences Behind the Eight Ball: Sex for Crack Cocaine Exchange and Poor Black Women documents an American tragedy that highlights the widening gap between social and economic classes. In their own words, poor black women?nameless, faceless, and marginalized by poverty?share the details of their lives before and after crack cocaine invaded their communities, each recalling the circumstances of her introduction to the drug and her first experience using sex to support her addiction. These candid.